INTRODUCTION TO THEORY-DRIVEN PROGRAM EVALUATION culturally responsive and strengths-focused... applications. - Donaldson, Stewart I. (Stewart Ian) ([S.l.] : ROUTLEDGE, 2021)
Introduction to Theory-Driven Program Evaluation provides a clear guide for practicing evaluation science, and numerous examples of how these evaluations actually unfold in contemporary practice. A special emphasis is placed how to conduct theory-driven program evaluations that are culturally responsive and strengths-focused. In this thoroughly revised new edition, author Stewart I. Donaldson provides a state-of-the art treatment of the basics of conducting theory-driven program evaluations. Each case follows a three-step model: developing program impact theory; formulating and prioritizing evaluation questions; and answering evaluation questions. The initial chapters discuss the evolution and popularity of theory-driven program evaluation, as well as step-by-step guide for culturally responsive and strengths-focused applications. Succeeding chapters provide actual cases and discuss the practical implications of theory-driven evaluation science. Reflections, challenges, and lessons learned across numerous cases from practices are discussed. The volume is of significant value to practicing evaluators, professors of introductory evaluation courses and their students, advanced undergraduate and graduate students, and serves as a text or a supplementary text for a wide range of evaluation and applied research courses. It is also of great interest to those interested in the connections between work and health, well-being, career development, human service organizations, and organizational improvement and effectiveness.
Keywords: Evaluation research (Social action programs); Public welfare -- Evaluation; Social service -- Evaluation; Quality of life -- Evaluation; Communication in social action; BUSINESS & ECONOMICS / Total Quality Management; EDUCATION / Evaluation; MEDICAL / Occupational & Industrial Medicine